2016
DOI: 10.1161/jaha.115.002555
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Reactive Oxygen Species Mediate Cardiac Structural, Functional, and Mitochondrial Consequences of Diet‐Induced Metabolic Heart Disease

Abstract: BackgroundMitochondrial reactive oxygen species (ROS) are associated with metabolic heart disease (MHD). However, the mechanism by which ROS cause MHD is unknown. We tested the hypothesis that mitochondrial ROS are a key mediator of MHD.Methods and ResultsMice fed a high‐fat high‐sucrose (HFHS) diet develop MHD with cardiac diastolic and mitochondrial dysfunction that is associated with oxidative posttranslational modifications of cardiac mitochondrial proteins. Transgenic mice that express catalase in mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 40 publications
6
80
0
Order By: Relevance
“…1D). Thus, under basal conditions HFHS feeding led to diastolic dysfunction with preservation of systolic function confirming our prior echocardiographic findings [10,11] and showing that this isolated heart preparation exhibits hemodynamic features consistent with MHD.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…1D). Thus, under basal conditions HFHS feeding led to diastolic dysfunction with preservation of systolic function confirming our prior echocardiographic findings [10,11] and showing that this isolated heart preparation exhibits hemodynamic features consistent with MHD.…”
Section: Resultssupporting
confidence: 90%
“…This was evident even at low LV volumes well within the physiologic range of LVEDP of 0–35 mm Hg. We previously showed that HFHS feeding for 4 months led to diastolic dysfunction in mice in vivo as reflected by abnormal LV filling and slowed LV relaxation measured by Doppler echocardiography [10]. The current ex vivo finding of impaired diastolic function in the isolated beating heart is consistent with our prior in vivo echocardiographic findings, showing that the diastolic dysfunction we observed in the isolated beating heart is of physiologic relevance.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations